1989
DOI: 10.1002/ep.3300080110
|View full text |Cite
|
Sign up to set email alerts
|

Testing of novel sorbents for H2S removal from coal gas

Abstract: Application of zinc ferrite, a regeneruble mixed metal oxide, for the removal of H2S from hot coal derived gas streams is limited to a maximum temperature of about 1,250"F (677°C) and to a minimum H2S concentration of about 5 ppmv in the cleaned gas. Four novel sorbents that have shown potential for ocercoming the limitations of zinc ferrite [ l , 41 were selected for development and bench-scale testing. Several variations of these mixed metal oxides were prepared, using different amounts of binders. They were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 0 publications
0
38
0
Order By: Relevance
“…58 Because of the apparent limitations of the zinc ferrite sorbent, many investigators have been conducting research to develop a superior mixed metal oxide sorbent. [42][43][44][45][59][60][61][62][63] Earlier experimental studies that pioneered the use of mixed-metal oxides were performed at the Massachusetts Institute of Technology (MIT), [64][65][66] Research Triangle Institute (RTI), 67 68 Electrochem, 69 44,45 has shown that titanium oxide is a better alternative to iron oxide additives in terms of the higher stability of the titanates over the ferrite compounds of zinc, and their similar sulfidation equilibria. With zinc titanates, the sulfidation temperature has been shown to extend to 700 °C, and sintering of the ZnO was greatly reduced.…”
Section: Sorbent Developmentmentioning
confidence: 99%
“…58 Because of the apparent limitations of the zinc ferrite sorbent, many investigators have been conducting research to develop a superior mixed metal oxide sorbent. [42][43][44][45][59][60][61][62][63] Earlier experimental studies that pioneered the use of mixed-metal oxides were performed at the Massachusetts Institute of Technology (MIT), [64][65][66] Research Triangle Institute (RTI), 67 68 Electrochem, 69 44,45 has shown that titanium oxide is a better alternative to iron oxide additives in terms of the higher stability of the titanates over the ferrite compounds of zinc, and their similar sulfidation equilibria. With zinc titanates, the sulfidation temperature has been shown to extend to 700 °C, and sintering of the ZnO was greatly reduced.…”
Section: Sorbent Developmentmentioning
confidence: 99%
“…Recently, progress in synthesis techniques has initiated new surge of concern in ferrites to improve their physical properties and develop their applications [1][2][3]. Zinc ferrite has long attracted researcher's interests because of its intriguing magnetic properties compared with other spinel ferrites.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, only a few metal oxides can meet all these stringent requirements simultaneously. Iron oxide [21], zinc oxide [22], copper oxide, as well as mixed-metal oxide compounds such as zinc titanates [23,24] and other copper-based [25) compounds have been investigated for use as regenerable sorbents in HGCU applications.…”
Section: Hgcu Randd Programs In the Usmentioning
confidence: 99%